2018
DOI: 10.1097/fch.0000000000000198
|View full text |Cite
|
Sign up to set email alerts
|

Do Infant Feeding Practices Differ Between Grandmothers and Mothers in Rural China? Evidence From Rural Shaanxi Province

Abstract: The overall goal of this study is to examine whether infant feeding practices differ between mothers and grandmothers in rural China. We randomly sampled 1383 caregivers of infants aged 18 to 30 months living in 351 villages across 174 townships in nationally designated poverty counties in rural areas. Results show that a high fraction of caregivers of 18- to 30-month-old children living in low-income areas of rural China do not regularly engage in positive infant feeding practices. Only 30% of children in our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 23 publications
1
38
1
Order By: Relevance
“…Relatives (such as grandmothers) and friends with children were the main source of caregivers' feeding knowledge even though they are unlikely to have access to better information and may have misinformed mothers, which is consistent with the previous studies [17][18][19]. Grandmothers are generally less educated, rely on traditional methods, and may not understand the importance of appropriate nutrition [19].…”
Section: Main Findingssupporting
confidence: 80%
See 2 more Smart Citations
“…Relatives (such as grandmothers) and friends with children were the main source of caregivers' feeding knowledge even though they are unlikely to have access to better information and may have misinformed mothers, which is consistent with the previous studies [17][18][19]. Grandmothers are generally less educated, rely on traditional methods, and may not understand the importance of appropriate nutrition [19].…”
Section: Main Findingssupporting
confidence: 80%
“…Although only 39% of mothers in the study areas followed child feeding official accounts, more than three-fourths were willing to receive feeding information in the format of text, pictures or videos through WeChat. WeChat feeding interventions should be mainly delivered to mothers because they are more like to consult external sources of feeding information [19], and mothers used WeChat more (80.8%) than grandparents (28.9%). Also, more than 80% of mothers in our study attended junior high school or above, while around 60% of grandparents were illiterate and could not read.…”
Section: Wechat Could Be a Potential Way To Deliver Infant Feeding Rementioning
confidence: 99%
See 1 more Smart Citation
“…23 Some studies found grandmothers are beneficial for child height 24 25 and educational participation, 26 while others found grandmothers have negative effects on child health, 27 feeding practices 21 and weight. 14 28 With few exceptions, [29][30][31][32][33] the majority of quantitative studies in LMIC of grandmother caregiving on child outcomes operationalise grandmother involvement crudely as household coresidence with the grandchild 13 14 21 22 26 34 35 or use proxies such as whether the grandmother is still alive. 25 36 37 Though studies have illuminated the impacts of grandmother presence [36][37][38] these crude measures do not operationalise the type, frequency or temporality of a grandmother's involvement with child caregiving activities.…”
Section: Bmj Global Healthmentioning
confidence: 99%
“…Again, no difference can be found in child health outcomes between attrited and non-attrited children.Overall, we can see that children in the attrition group tend to be only children and to be cared for by grandmothers rather than mothers. Although attrited children were more likely to be taken care of by grandmothers compared with non-attrited samples—which could be negatively associated with a child’s development outcomes [68]—mothers also count for the larger share of primary caregivers in our sample, both before and after attrition. Mothers of attrited children also tend to be more educated, indicating a slightly higher socioeconomic status.…”
Section: Table A1mentioning
confidence: 99%